Investigation of a Large-Mode-Area Fiber Designed for 2.0 μm Based on Multi-Layer Holes Resonance - Xiao Shen; Yifei Sun; Meimei Kong; Wei Wei (IEEE Photonics Journal, 2023)
This work proposes a novel large mode area fiber with multi-layer holes of 2.0 μm based on electromagnetic field theory and finite element analysis. Modifying the structure parameters can reduce the fundamental mode confinement loss to less than 0.1 dB/m, and the lowest high-order mode confinement loss may be greater than 10.0 dB/m. The fiber has exceptional single-mode transmission performance due to its high loss ratio. The effective mode field area is 3849 μm2, and the single mode core diameter is 80.0 μm. To obtain a larger mode field diameter, the construction used here includes a smaller cladding diameter in the already available large mode field fiber. The cladding parameters may be changed independently, making it convenient and adaptable to obtain the best simulation results. Compared to the large-mode field fiber standard, which has excellent single mode operation performance, the loss ratio of this design is substantially larger. Additionally, it can effectively sustain single mode operation when the wavelength shifts from 1.65 to 2.10 μm, which is advantageous for developing 2.0 μm fiber lasers.